Registration errors among patients receiving blood transfusions: a national analysis from 2008 to 2017. Issue 2 (30th September 2020) - Vijenthira, Shangari; Armali, Chantal; Downie, Helen; Wilson, Ann; Paton, Kathy; Berry, Brian; Wu, Hong‐Xing; Robitaille, Ann; Cserti‐Gazdewich, Christine; Callum, Jeannie
Abstract : Background and objectives: The key first step for a safe blood transfusion is patient registration for identification and linking to past medical and transfusion history. In Canada, any deviation from standard operating procedures in transfusion is an error voluntarily reportable to a national database (Transfusion Error Surveillance System [TESS]). We used this database to characterize the subset of registration‐related errors impacting transfusion care, including where, when and why the errors occurred, and to identify frequent high‐risk errors. Materials and methods: A retrospective analysis was conducted on transfusion errors reported to TESS by sentinel reporting sites relating to patient registration and patient armbands, between 2008 and 2017. Free‐text comments describing the error were coded to further categorize into common error types. The number of specimens received in the transfusion laboratory was used as the denominator for rates to allow for comparison between hospital sites. Results: Five hundred and fifty‐four registration errors were reported from 10 hospitals, for a global error rate of 5·4/10 000 samples (median 5·0 [interquartile range 3·7–7·0]). The potential severity was high in 85·7% of errors ( n = 475). The patient experienced a consequence in 10·8% of errors ( n = 60), but none resulted in patient harm. Rates varied widely and differed by nature across sites. Errors most commonly occurred in outpatient clinics or procedure units ( n = 160, 28·8%) and in emergency departments ( n = 130, 23·5%). Conclusion: Registration errors affect transfusion at every step and location in the hospital and are commonly high risk. Further research into common root causes is warranted to identify preventative strategies.